2011
DOI: 10.1111/j.1365-2559.2011.03993.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of embryonic stem cell-associated genes Oct4, Sox2 and Nanog in human gliomas

Abstract: The present findings suggest that ESC-associated pathways are activated in human gliomas and that these may be involved in glioma progression, a role that is distinct from that in ESCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
151
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(168 citation statements)
references
References 59 publications
13
151
0
4
Order By: Relevance
“…Aided by FACS, we isolated CD146-enriched U87MG cells and demonstrated that these subpopulations show increased EMT and CSC traits. First, we observed that U87MG (++) cells presented higher expression of the stem cell markers Oct4, Sox2, Nanog, and LGR5 (27,31) and exhibited increased levels of both Slug and β-Catenin, overexpression of which have been proven sufficient to repress E-cadherin and drive EMT (8). Further, evaluation of prolonged in vitro exposure to YY146 in U87MG cells indicated that YY146 treatment reduces both mRNA and proteins levels of CD146 and foments the reversal of CSC and EMT phenotypes through the reactivation of E-cadherin expression and abrogation of migratory properties.…”
Section: Discussionmentioning
confidence: 93%
“…Aided by FACS, we isolated CD146-enriched U87MG cells and demonstrated that these subpopulations show increased EMT and CSC traits. First, we observed that U87MG (++) cells presented higher expression of the stem cell markers Oct4, Sox2, Nanog, and LGR5 (27,31) and exhibited increased levels of both Slug and β-Catenin, overexpression of which have been proven sufficient to repress E-cadherin and drive EMT (8). Further, evaluation of prolonged in vitro exposure to YY146 in U87MG cells indicated that YY146 treatment reduces both mRNA and proteins levels of CD146 and foments the reversal of CSC and EMT phenotypes through the reactivation of E-cadherin expression and abrogation of migratory properties.…”
Section: Discussionmentioning
confidence: 93%
“…At the top hierarchy of the Jak-Stat3 signaling pathway, OCT4, SOX2 and NANOG, are considered to serve the most important function in maintaining ESC properties (20). Previously, increased glioma progression was identified to be associated with upregulated OCT4, SOX2 and NANOG (21,22). Additionally, combinatorial expression levels of OCT4, NANOG and SOX2 were positively associated with increasing glioma malignancy (22).…”
Section: Discussionmentioning
confidence: 99%
“…An embryonic stem cell gene signature is well known to correlate with a more undifferentiated phenotype in various cancers (28), and a large scale tissue microarray analysis including 80 low-grade and 98 high-grade gliomas showed an upregulated protein level of NANOG, KLF-4, OCT-4 and SOX-2 in highgrade gliomas (29). Several other studies also point to the relevance of neural and embryonic stem cell markers in GBM progression (30)(31)(32)(33)(34)(35)(36). In the present study we showed that both neural and embryonic stem cells markers are preferentially co-expressed with CXCR4 in matched samples of primary and recurrent GBM pairs, whereas CXCR7 was mostly found on stem cell marker negative cells.…”
Section: Discussionmentioning
confidence: 99%